1985
DOI: 10.1126/science.3992248
|View full text |Cite
|
Sign up to set email alerts
|

A Sexually Dimorphic Nucleus in the Human Brain

Abstract: A sexually dimorphic cell group is described in the preoptic area of the human hypothalamus. Morphometric analysis revealed that the volume of this nucleus is 2.5 +/- 0.6 times (mean +/- standard error of the mean) as large in men as in women, and contains 2.2 +/- 0.5 times as many cells. Between the ages of 10 and 93 years, the nucleus decreases greatly in volume and in cell number. Although no function has yet been established for this nucleus, it is located within an area that is essential for gonadotropin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
160
1
5

Year Published

1993
1993
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 482 publications
(173 citation statements)
references
References 24 publications
7
160
1
5
Order By: Relevance
“…The fact that they could not find a sex difference in INAH1 (= SDN-POA), as found by us (63), could be fully explained by the strong age effect on the sex differences of this nucleus (58,65). In fact, the sex difference develops only after the age of 5 years and disappears temporarily after the age of 50 years (63,66,67 (63). Further analysis of INAH1 and 2 in the transsexual population is ongoing, and confirms the presence of a clear sex difference in adult controls up to 50 years of age.…”
Section: Sex Differences In the Human Brainmentioning
confidence: 52%
See 2 more Smart Citations
“…The fact that they could not find a sex difference in INAH1 (= SDN-POA), as found by us (63), could be fully explained by the strong age effect on the sex differences of this nucleus (58,65). In fact, the sex difference develops only after the age of 5 years and disappears temporarily after the age of 50 years (63,66,67 (63). Further analysis of INAH1 and 2 in the transsexual population is ongoing, and confirms the presence of a clear sex difference in adult controls up to 50 years of age.…”
Section: Sex Differences In the Human Brainmentioning
confidence: 52%
“…In the current review we focus on the sex differences in the human hypothalamus and adjacent areas. When observed by our group, the structural difference in the intermediate nucleus of the human hypothalamus (InM) (60-62) was at first termed "the sexually dimorphic nucleus of the preoptic area (SDN-POA)" (63). We found this nucleus to be 2.5 times larger in men than in women and to contain 2.2 times as many cells (63).…”
Section: Sex Differences In the Human Brainmentioning
confidence: 69%
See 1 more Smart Citation
“…In humans, postmortem studies have also discovered several sexually dimorphic nuclei with higher cell numbers and larger volume in males within this region (Allen et al, 1989;Swaab and Fliers, 1985). Clusters of enlarged hypothalamic volume in men as well as in adolescent boys have also been detected in vivo (Goldstein et al, 2001;Lombardo et al, 2012).…”
Section: Discussionmentioning
confidence: 95%
“…Another group reported that SDN-POA lesions in male rats decreased the percentage of animals that ejaculated in a mating test, and increased latencies to mount, intromit, or ejaculate [41]. Although an exact homolog of the SDN-POA may not exist in other species, there is evidence for sexual dimorphism of the anterior hypothalamus and preoptic area in other species that have been studied [152,22,111,2], making the SDN-POA of the rat a valuable comparative model.…”
Section: Sexually Dimorphic Nucleus Of the Preoptic Area (Sdn-poa)mentioning
confidence: 99%